PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE DALAM PENDIDIKAN DIGITAL: PELUANG, TANTANGAN, DAN IMPLIKASINYA TERHADAP MASA DEPAN PENDIDIKAN - Mohamad Tohadi Irfan; Muhammad Davit Priatama; Maruli Simbolon; Nilawati Tadjudin; Andi Warisno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed digital education by introducing innovations that support more effective, adaptive, and personalized learning processes. This article aims to analyze the opportunities, challenges, and implications of AI implementation for the future of education through a Systematic Literature Review (SLR) approach. The research data were collected from scientific articles, academic books, reports from international organizations, and other relevant publications discussing AI in digital education. The review process involved identification, selection, evaluation, and synthesis of the literature to provide a comprehensive understanding of current research developments. The findings reveal that AI offers numerous opportunities, including supporting adaptive learning, improving assessment efficiency, expanding access to education, strengthening data-driven decision-making, and assisting educators in designing more personalized learning experiences. However, the implementation of AI also faces several challenges, such as limited AI literacy, technological access disparities, ethical and academic integrity concerns, and issues related to data security and privacy. Furthermore, AI encourages a paradigm shift in education by redefining teachers’ roles as facilitators and mentors within digital learning ecosystems. Therefore, enhancing digital competencies, developing adaptive policies, and establishing appropriate regulations are essential to ensure that AI contributes to high-quality, inclusive, and sustainable education in the future.